NATO Archives Online: a source system for the history of international relations - Valacchi, Maddalena (Bibliothecae.it, 2022)
This article aims to evaluate the nature, structure and potential of the digital archives of the North Atlantic Treaty Organization (NATO) not only from the archival point of view but also for their usefulness in the frame of the history of international relations. The first part of the work deepens the context of the history of international relations, starting from the definition of the discipline and then reflecting -in a general way- on the types of archival sources available in this regard. In this sense, it will be proposed a brief review of the historical evolution of the concept of diplomatic sources, analysing their characteristics and fields of application in relation to the nature of the different producers involved. Then the work shifts to the specific physiognomy of the NATO archives, focusing on the profile of the producer and the characteristics of the digital documentary material available. In this paragraph, therefore, we try, first of all, to provide an exhaustive description of NATO, from its historical origins to its legal evolution, up to the role it plays today in a post-Cold War world. Subsequently, a description of the funds available online is provided. This description is supplemented by the elements necessary to evaluate and allow the use of these sources both from a technical-archival point of view and from that of the history of international relations. Finally, the last part reflects on the physiognomy of a web-based archive and on the potential that it could expresses, highlighting opportunities and critical issues.